2013
DOI: 10.1371/journal.pone.0079067
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Function of CD34+ Cells by Targeting Plasminogen Activator Inhibitor-1

Abstract: Previously, we showed that transient inhibition of TGF- β1 resulted in correction of key aspects of diabetes-induced CD34+ cell dysfunction. In this report, we examine the effect of transient inhibition of plasminogen activator inhibitor-1 (PAI-1), a major gene target of TGF-β1 activation. Using gene array studies, we examined CD34+ cells isolated from a cohort of longstanding diabetic individuals, free of microvascular complications despite suboptimal glycemic control, and found that the cells exhibited reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
14
0
2
Order By: Relevance
“…This is not the first report on the importance of miRs in improving the function of CD34 + cells in the context of disease. A recent study showed that miR-92a corrects CD34 + cell dysfunction in diabetes by reducing the inflammatory phenotype of these cells (77), and the use of miR-146a to target plasminogen activator inhibitor-1 results in enhanced in vitro growth and migration of diabetic CD34 + cells (42). Given that CD34 + cells from donors with disease typically exhibit reduced number and function, a biomaterial culture strategy, such as the one reported herein, may be used to mediate proangiogenic miRs and improve the potency of such cells for autologous use in therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not the first report on the importance of miRs in improving the function of CD34 + cells in the context of disease. A recent study showed that miR-92a corrects CD34 + cell dysfunction in diabetes by reducing the inflammatory phenotype of these cells (77), and the use of miR-146a to target plasminogen activator inhibitor-1 results in enhanced in vitro growth and migration of diabetic CD34 + cells (42). Given that CD34 + cells from donors with disease typically exhibit reduced number and function, a biomaterial culture strategy, such as the one reported herein, may be used to mediate proangiogenic miRs and improve the potency of such cells for autologous use in therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mobilization agents are effective at increasing the number of circulating CD34 + cells (reviewed in ref. 40), whereas in vitro cell culture expansion and genetic manipulation and stimulation have been tested to improve the yield and functionality of the cells (41)(42)(43)(44)(45)(46)(47). Notably, it has been shown that overexpression of the secreted angiogenic morphogen sonic hedgehog by CD34 + cells resulted in a superior therapy for treating myocardial infarction by limiting the infarct size and increasing vascular density (43).…”
mentioning
confidence: 99%
“…In this study, we demonstrate the critical role of ATM maintenance in the clinical setting by using a unique cohort of diabetic individuals protected from DR. We have previously reported that this patient population showed an increase in the protective arm of the renin‐angiotensin axis (Ang1‐7 and MAS1) and decease in TGF‐β1 expression . This study identifies a novel mechanism of protection of CD34 + cells from diabetic stress by recognizing the critical role of ATM in the long‐term survival of HSCs.…”
Section: Discussionmentioning
confidence: 75%
“…However, circulating angiogenic cells of diabetics, such as CD34 + cells, typically lose this ability and secrete proinflammatory and vasoconstrictive factors . Additionally, diabetic circulating angiogenic cells lose their ability to migrate into tissues in response to local injury .…”
Section: Discussionmentioning
confidence: 99%